Electronic litigation by filing an electronic lawsuit - Guiaman, Muhalidin Usman; Al- Omari, Mahmoud Ali (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to demonstrate the possibility of benefiting from the great scientific development in the field of technology, especially the Internet in the field of litigation by filing an electronic lawsuit, as overcrowding in the courts is reduced.Also electronic litigation provides speed and accuracy in issuing judgments and ease of access to the proceedings of the case with ease and ease, in addition to saving the time it achievers in terms of movement, wages, and so on.The study also shows the characteristics and controls that it provides when using electronic litigation as an emerging method, as well as clarifying the difficulties facing this type of litigation, and how these difficulties can be faced.And the issue of electronic litigation referred to by the jurists, is one of the possibilities that were available in their time, and what they found from the customs, and they sat that in their books, and it is the duty of the rules of Muslims to organize the affairs of the judiciary, which guarantees justice and equality between the opponents with the independence of all the means available in each era and including it does not violate the provisions of Sharia Islamic.In this study, the researcher followed several approaches, most notably: the descriptive approach, by tracing the terms mentioned in the research and between them, as well as the deductive approach by looking at the legal legislation regulating the comparative approach to see the experiences of the countries used for this litigation to determine the nature of, This system.One of the results of this study is that it notes the Jordanian legislation in regulating the rules of electronic litigation, and one of these shortcomings is the failure to devote sufficient guarantees to the framework of the application of electronic litigation procedures, the failure to provide for electronic litigation procedures, especial in civil matters, and the failure to address the authoritative rulings issued and its framework.The researcher recommended that the electronic litigation process needs accuracy and control that should be used without excessive, in order to prove its success in the hoped manner, and that this type of litigation needs specialized technical cadres to assist during the course of the trials.
Keywords: litigation; electronic; lawsuit